Sustainability reporting, liquidity, and audit report lag: Evidence from Indonesian mining companies - Nathania Rachel Queen Rondonuwu; Jullie Jeannete Sondakh; ⁠Anneke Wangkar (The Contrarian : Finance, Accounting, and Business Research, 2026)
The interval between a company's fiscal year-end and the issuance date of the independent auditor's report or Audit report lag (ARL) is a critical indicator of financial reporting timeliness. Despite growing environmental, social, and governance (ESG) disclosure requirements in Indonesia, empirical evidence on how sustainability reporting quality influences audit timeliness in the extractive sector remains limited and inconclusive. Drawing on Signaling Theory (Spence, 1973) and Agency Theory (Jensen & Meckling, 1976), this study examines the effects of sustainability reporting and liquidity on audit report lag in mining companies listed on the Indonesia Stock Exchange (IDX) during 2022–2024. A quantitative, associative approach was employed with purposive sampling, yielding 41 companies and 123 firm-year observations. Data were analyzed using panel data regression with Fixed Effects and Random Effects models (Hausman test applied), incorporating control variables (firm size, profitability, leverage, and auditor type). The results show that sustainability reporting does not significantly affect audit report lag, while liquidity has a significant positive effect on audit report lag. The liquidity finding suggests that companies with higher current asset volumes require more extensive audit procedures, thereby prolonging the audit process. These findings contribute to the ARL literature by providing sector-specific evidence from the Indonesian mining industry and offer practical implications for audit planning and corporate governance.